Bifidobacterium longum subsp. infantis CCFM1269 promotes intestinal barrier and release of IFN-β through TLR4-TRIF dependent way in growing mice - Mengfan Ding; Bo Yang; Bowen Li; Haiqin Chen; Renqiang Yu; Ross R. Paul; Catherine Stanton; Shilong Jiang; Jianxin Zhao; Wei Chen (Food Science and Human Wellness)
Bifidobacterium longum subsp. infantis is a commensal bacterium that predominates in the infant gut, playing a critical role in both preventing foreign infections and facilitating immune development. This study aimed to explore the effects of B. longum subsp. infantis supplementation on interferon-beta (IFN-β) secretion and intestinal barrier improvement in growing mice. Female and male mice were orally administered either saline or B. longum subsp. infantis CCFM1269 or I5TI (1 × 109 CFU/mice per day, n = 8) from 1-week-age until 3-, 4-, and 5-week-age. RNA sequencing analysis revealed that CCFM1269 exhibited potential antiviral capacity through increasing 2’-5’ oligoadenylate synthetase (OAS). Additionally, CCFM1269 supplementation significantly increased colonic IFN-β levels which combined with OAS in 3-week-old female and male mice by activating the TLR4-TRIF-dependent signaling pathway. However, this effect was not observed in 4- and 5-week-old mice. Furthermore, both CCFM1269 were found to modulate the gut microbiota composition and enhance the intestinal barrier function in 3-, 4-, and 5-week-old mice. In summary, the results of this study suggested that B. longum subsp. infantis CCFM1269 promoting intestinal barrier and releasing IFN-β in growing mice was in a strain-specific and time-dependent manner.